Asymmetric Epoxidation of Olefins Catalyzed by Substituted Aminobenzimidazole Manganese Complexes Derived from L‐Proline. Issue 3 (10th November 2021) - Tian, Jing; Lin, Jin; Zhang, Jisheng; Xia, Chungu; Sun, Wei
Abstract: A family of manganese complexes [Mn( R peb)(OTf)2 ] (peb=1‐(1‐ethyl‐1 H ‐benzo[ d ]imidazol‐2‐yl)‐ N ‐((1‐((1‐ethyl‐1 H ‐benzo[ d ]imidazol‐2‐yl)methyl) pyrrolidin‐2‐yl)methyl)‐ N ‐methylmethanamine)) derived from L ‐proline has been synthesized and characterized, where R refers to the group at the diamine backbone. X‐ray crystallographic analyses indicate that all the manganese complexes [Mn( R peb)(OTf)2 ] exhibit cis ‐ α topology. These types of complexes are shown to catalyze the asymmetric epoxidation of olefins employing H2 O2 as a terminal oxidant with up to 96% ee. Obviously, the R group of the diamine backbone can influence the catalytic activity and enantioselectivity in the asymmetric epoxidation of olefins. In particular, Mn( i‐Pr peb)(OTf)2 bearing an isopropyl arm, cannot catalyze the epoxidation reaction with H2 O2 as the oxidant. However, when PhI(OAc)2 is used as the oxidant instead, all the manganese complexes including Mn( i‐Pr peb)(OTf)2 can promote the epoxidation reactions efficiently. Taken together, these results indicate that isopropyl substitution on the R peb ligand inhibits the formation of active Mn(V)‐oxo species in the H2 O2 /carboxylic acid system via an acid‐assisted pathway. Abstract :